Antichaperone activity and heme degradation effect of methyl tert‐butyl ether (MTBE) on normal and diabetic hemoglobins. Issue 5 (5th December 2016) - Najdegerami, Ismaeil Hossein; Maghami, Parvaneh; Sheikh‐Hasani, Vahid; Hosseinzadeh, Ghader; Sheibani, Nader; Moosavi‐Movahedi, Ali A.
Abstract: Because of the extensive use of methyl tert ‐butyl ether (MTBE) as an additive to increase the octane quality of gasoline, the environmental pollution by this compound has increased in recent decades. Environmental release of MTBE may lead to its entry to the blood stream through inhalation or drinking of contaminated water, and its interactions with biological molecules such as proteins. The present study was proposed to comparatively investigate the interactions of MTBE with hemoglobin (Hb) from diabetic and nondiabetic individuals using various spectroscopic methods including UV‐visible, fluorescence, chemiluminescence, and circular dichroism. These results demonstrated the effects of MTBE on heme degradation of Hb and the reaction of these degradation products with water generating reactive oxygen species. Interaction of Hb with MTBE enhanced its aggregation rate and decreased lag time, indicating the antichaperone activity of MTBE upon interaction with Hb. Furthermore, the diabetic Hb showed more severe effects of MTBE, including heme degradation, reactive oxygen species production, unfolding, and antichaperone behavior than the nondiabetic Hb. The results from molecular docking suggested that the special interaction site of MTBE in the vicinity of Hb heme group is responsible for heme degradation. Abstract : Methyl tert‐butyl ether, because of its special interaction cite, induces hemoglobin unfolding through degradation of heme and subsequent reactive oxygen species generation.